Strategi Implementasi Manajemen Pendidikan Inklusif di Sekolah Menengah: Studi Kasus di SMP Negeri 4 Babelan - Julinda Siregar; Novita Trianah; Ceni Liswati; Saptiawati Saptiawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to describe and analyze the implementation of inclusive education management at SMP Negeri 4 Babelan. Inclusive education is an educational approach that provides learning opportunities for all students without discrimination, including those with special educational needs (ABK). This concept emphasizes the importance of a friendly, adaptive, and responsive learning environment to student diversity. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Informants in this study consisted of the principal, regular teachers, special assistant teachers, students with special needs, and their parents. The results of the study indicate that inclusive education management at SMP Negeri 4 Babelan has been implemented through four main management functions, namely: (1) strategic planning integrated into the annual school work program, including budget allocation for inclusion needs; (2) organizing an inclusion team involving teachers, education staff, and the school committee; (3) implementing adaptive learning based on a differentiation and individualization approach, adjusted to students' abilities and learning styles; and (4) evaluations conducted periodically to assess students' academic and social-emotional development, as well as the effectiveness of the inclusion program as a whole. However, this study also identified several obstacles, including a limited number of special assistant teachers, a lack of professional training for regular teachers, and a lack of supporting facilities such as therapy rooms or learning aids. Furthermore, factors supporting the program's success include the school leadership's commitment to mainstreaming inclusion, a collaborative spirit among teachers, and the support and active involvement of parents. Based on these findings, this study recommends several strategic steps, such as strengthening teacher training in inclusive classroom management and adding special assistant teachers as needed.